2017
DOI: 10.11648/j.ajpc.20170605.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adsorption Capacity of Methylene Blue in Aqueous Medium by Two Adsorbents: The Raw Hull of <i>Lophira Lanceolata</i> and Its Activated Carbon

Abstract: Abstract:The purpose of this study is to evaluate the adsorption capacity of two adsorbents from the lignocellulosic residues of Lophira Lanceolata. The raw hull of Lophira Lanceolata and its activated carbon produced by chemical activation with orthophosphoric acid (H 3 PO 4 ) at 50% (Vacid/V water ) of the said hull. The ratio of impregnation to orthophosphoric acid used is 4.5. Activation and carbonization were carried out at 400°C. The physicochemical properties of the prepared activated carbon were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Generally, the equilibrium was achieved within approximately the first hour of adsorption, indicating a favorable interaction between the methylene blue dye and BFS-ACs. These results were similar to those reported by some previous studies [8,15,25,46].…”
Section: Effect Of Contact Time On Methylene Blue Adsorptionsupporting
confidence: 93%
See 1 more Smart Citation
“…Generally, the equilibrium was achieved within approximately the first hour of adsorption, indicating a favorable interaction between the methylene blue dye and BFS-ACs. These results were similar to those reported by some previous studies [8,15,25,46].…”
Section: Effect Of Contact Time On Methylene Blue Adsorptionsupporting
confidence: 93%
“…In order to minimize this dye's impacts on the environment, many technologies have been developed to treat wastewater such as flocculation, coagulation, ozonation, chlorination, anodic oxidation, and electrooxidation. However, these techniques are costly and frequently become secondary sources of pollution [8]. Many studies revealed that adsorption by solid adsorbents presents the advantages of high efficiency, simple design, and low initial costs [7].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of adsorbent dosage on Methylene blue was determined at room temperature (298 K), adsorbent concentration (100 mg/L) and time (15 minutes). The result, as presented in Figure 11 showed an increase in adsorption as the dosage increases [58,59,60] up to 0.7 g. The increase may be due to the availability of a larger active surface area [61] and pore size. Maximum adsorptions of 99.207% and 89.997% were observed at 0.7 g for RTA and RTB respectively.…”
Section: Effect Of Biochar Dosagementioning
confidence: 93%
“…The cleaned charcoal sample was dried at 105 °C and subsequently activated at 250 °C for 24 h in an oven, then allowed to cool in the desiccator. The dried sample was powdered and sieved using different micrometers aperture sieve sizes (29,30).…”
Section: Carbonization Of Pomegranate Peelmentioning
confidence: 99%